(untitled) (Revista Espinhaço, 2017)
The present article aims to present the integrated and interdisciplinary analyzes that were carried out in the Sampaio archaeological site, municipality of Felício dos Santos, Minas Gerais state, Brazil. It is a shelter under rock implanted in average slope in the basin of the Araçuaí River, northeast of Minas Gerais, in the biome of the Brazilian cerrado. Excavated by the LAEP / UFVJM team, an important lithic artefatual set was exhumed, besides the identification of several combustion structures, being that the structure 03 obtained chronology of 4280 ± 30 y BP, an important date for the discussions of human occupations in the Brazilian Central Plateau. In addition, the site presents a rock art set of extreme relevance, generally associated with the Plateau Rock Art Tradition. Thus, the text will discuss the results of the analysis of the archaeological site (from prospecting, excavation and laboratory activities), presenting regional geoenvironmental data, analyzes of its cultural repertoire and chronology.